Interleukin 7 receptor ligation stimulates tyrosine phosphorylation, inositol phospholipid turnover, and clonal proliferation of human B-cell precursors. - Uckun, F M (1991)
Functional interleukin 7 (IL-7) receptors are expressed on the surface of multiphenotypic, biphenotypic, and immature B-lineage human lymphoid precursor cells with germ-line immunoglobulin heavy-chain genes but not on more mature B-lineage lymphoid cells with rearranged and/or expressed immunoglobulin heavy-chain genes. Thus, IL-7 may have an important regulatory role during the earliest stages of human B-cell ontogeny. The engagement of the surface IL-7 receptors on immature B-cell precursor cells with recombinant human IL-7 (rhIL-7) results in enhanced tyrosine phosphorylation of multiple phosphoproteins, stimulates inositol phospholipid turnover and DNA synthesis, and promotes their clonal proliferation. These effects are (i) specific for rhIL-7, since rhIL-3, rhIL-4, rhIL-5, rhIL-6, and recombinant human granulocyte colony-stimulating factor do not elicit similar activities on IL-7 receptor-positive human pro-B cells; and (ii) mediated by IL-7 receptors, since they are not observed in IL-7 receptor-negative B-lineage lymphoid cell populations. rhIL-7-induced tyrosine phosphorylation on the 35-, 53-, 55-, 62-, 69-, 76-, 94-, 150-, 170-, and 190-kDa substrates as well as rhIL-7-induced stimulation of inositol phospholipid turnover are abrogated by the tyrosine kinase inhibitor genistein. These results demonstrate that the IL-7 receptor on immature human B-cell precursor populations is intimately linked to a functional tyrosine kinase pathway and tyrosine phosphorylation is an important and perhaps mandatory step in the generation of the IL-7 receptor-linked transmembrane signal.